2019
DOI: 10.3389/fendo.2019.00346
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Female Fertility: An Interdependent Correlation

Abstract: Besides aging, a number of non-modifiable lifestyle-related factors, such as smoking, elevated consumption of caffeine and alcohol, stress, agonist sports, chronic exposure to environmental pollutants, and other nutritional habits exert a negative impact on a women's fertility. In particular, metabolic disorders including diabetes, obesity, and hyperlipidemia commonly associated to hypercaloric diets are suspected to affect a woman's fertility either by direct damage to oocyte health and differentiation, or by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 73 publications
1
76
0
5
Order By: Relevance
“…It should be noted that estrogens and progesterone are transported in the blood by binding to albumin and specific sex hormone-binding globulins. The attachment of the hormones to this protein are so weak that they are released to the tissues over a period of approximately 30 min (38). Hence, it can be concluded that in the present study, liver function was normal in terms of albumin pathway.…”
Section: Discussionmentioning
confidence: 45%
“…It should be noted that estrogens and progesterone are transported in the blood by binding to albumin and specific sex hormone-binding globulins. The attachment of the hormones to this protein are so weak that they are released to the tissues over a period of approximately 30 min (38). Hence, it can be concluded that in the present study, liver function was normal in terms of albumin pathway.…”
Section: Discussionmentioning
confidence: 45%
“…Artigo de caso controle. De acordo com Silvestris et al (2019) uma ingestão adequada em macronutrientes, antioxidantes e folato na dieta diária fornecem benefícios essenciais para uma ótima saúde reprodutiva feminina e reduz o risco de infertilidade. Desta forma, é percebido que uma alimentação equilibrada e composta por macronutrientes e micronutrientes juntamente com bons hábitos no estilo de vida atuam na melhora da infertilidade da mulher, causando efeitos Research, Society and Development, v. 9, n. 9, e964998062, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.8062 positivos para uma concepção bem sucedida, além de prevenir riscos de aborto e complicações durante o parto.…”
Section: Resultados Mais Relevantesunclassified
“…Infertile women are therefore counseled to maintain a healthy eating habit to avoid accumulation of body fats with may impair ovulation (van Oers et al, 2016). The evaluation of lifestyle habits and the modification of unhealthy habits by trained health providers with specific management, like systematic folic acid supplementation in females attempting to conceive may yield the desired outcomes (Silvestris et al, 2019). High insulin levels and insulin resistance are associated with body fat accumulation, polycystic ovarian syndrome, metabolic syndrome, and all have serious implications for female infertility.…”
Section: Delayed Child Bearing /Age Of Starting a Familymentioning
confidence: 99%
“…The role of lifestyle factors in the etiology of infertility has generated a growing interest among researchers. Several authors have provided evidence of an association between lifestyle behaviors and infertility in both men and women, they include; delayed childbearing due to pursuit of career or education, age of starting a family, smoking, eating of fat-rich diets, alcohol and caffeine consumption, exercise, risky sexual behaviors, drug misuse, anxiety/depression, cellular phones and radiation among others (Araoye, 2003;Fehintola et al, 2017;Adewumi, 2017;Ilacqua et al, 2018;Durairajanayagam, 2018;Silvestris et al, 2019;Emokpae and Chima, 2018;Ikyernum et al, 2019;Alabi, 2020) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%